MODIFICATION OF THE INGENHOUSZ TRIAL TOOL TO IMPROVE THE EFFECTIVENESS AND EFFICIENCY OF PHOTOSYNTHESIS LEARNING IN CLASS VIII-3 STUDENTS SMP NEGERI 4 PALANGKA RAYA - Unru Maleh (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
The purpose of this study was to determine the effectiveness and efficiency of photosynthesis learning by using the modified Ingenhousz Experiment Tool that was made by researchers. The subjects in this study were students of SMP Negeri 4 Palangka Raya, grade VIII-3 Academic Year 2019/2020, with the total number of 23 students, consisting of 14 men and 9 women. Data collection for learning effectiveness was by using knowledge test sheets, performance and activities tests, while for learning efficiency by calculating the use of time in learning, product tests and questionnaires. Data on the effectiveness and efficiency of learning in the meeting-I and meeting-II were compared to determine the improvement. Based on the results of research, obtained that the use of the Ingenhousz Experiment Tool in photosynthesis learning resulted in an increase in learning outcomes, namely the average grade for knowledge rose from 56.69 to 80.86. Grade completeness increased from 34% to 90%. For the skills to carry out the experiment, the average grade increased from 63.00 to 78.52 and grade completeness skills rose from 22% to 95.65%. While for the average value of student activity increased from 2.57 to 2.85 in the good category. The ability of students to make Ingenhousz experimental equipment was 76.21 which was included in a good category, while the students' response to the learning process reached of 89%, which meant that the response of students was very good. The time spent could also be saved from 60 minutes to 45 minutes with the above results. It could be concluded that the modified Ingenhousz Experiment Tool increased the effectiveness and efficiency of the implementation of photosynthesis learning in grade VIII-3 of SMP Negeri 4 Palangka Raya